(untitled) - Agrios, George N. (London, 2005)
This fifth edition of the classic textbook in plant pathology outlines how to recognize, treat, and prevent plant diseases. It provides extensice coverage of abiotic, fungal, viral, bacterial,nematode and other plant diseases and their associated epidemiology. It also covers the genetics of resistance and modern management on plant disease. Plant Pathology, 5th Edition, is the most comprehensive resource and textbook that professionals, faculty and students can consult for well-organized, essential information. This thoroughly revised edition is 45% larger, covering new discoveries and developments in plant pathology and enhanced by hundreds of new color photographs and illustrations.
Thâm cứu sinh lý và sinh thái của nấm hại cây trồng,Thâm cứu bảo vệ thực vật,Tương tác giữa cây trồng và vi sinh vật,Vi khuẩn học thực vật,Tương tác giữa cây trồng và VSV,Sinh lý và sinh thái của nấm,Sự phát sinh bệnh,Bệnh hại sau thu hoạch,Chiến lược quản lý bệnh hại cây trồng,Dịch bệnh của cây trồng,Bệnh trong đất của cây trồng,Bệnh trong đất của cây trồng,Chiến lược quản lý dịch hại cây trồng,Thâm cứu giám định bệnh hại cây trồng,Bệnh hại trên nông sản,Anh văn chuyên môn - KHCT,Bệnh cây trồng,Bệnh trong đất của cây trồng
Keywords: Plant diseases